Best Proximity Points of (A, S, p)-contractions in the Framework of w-distance (European Journal of Pure and Applied Mathematics, 2026)
Shahzad et al. [RACSAM 111 (2017) 307-324] introduced the notion of $(\mathcal{A,S})$- contractions which unifies several well known nonlinear type contractions (e.g. $\mathcal{R}$-contractions, $\mathcal{Z}$-contractions, $\mathcal{L}$-contractions etc.) in one go.In this paper we extend the notion of $(\mathcal{A,S})$-contractions from Shahzad et al. \cite{S} to non-self mappings in a metric space with a $w$-distance. Then we prove some new proximity point theorems for the aforementioned type of mappings. This paper is a continuation of our previous papers \cite{Ko2,Ko1}.
Keywords: Fixed point; w-distance; (A,S)-contraction; best proximity point